STUDY OF A VARIETY OF CAULIFLOWER HYBRIDS BY DIRECT SOWING CULTURE - Gr. Ardelean; Al. S. Apahidean; Al. I. Apahidean (Agricultura, 2013)
The cultivar is a key factor in vegetable production and the financial result largely depends on it. Cultivar can influence the level of production achieved, the commercial aspect and the period in which production is obtained. Choosing the right cultivar should take into account the specific ecological zone were the culture is performed. Cauliflower cultures are started mainly by seedlings, but there are concerns for its cultivation, in some cases, by direct sowing. Transylvania climatic conditions are favorable for growing cauliflower mostly during spring and autumn when temperatures are favorable for the formation of quality inflorescences. The experience took place in 2012, in the Reghin, Mures County. In the experimental culture, started by direct sowing, the following varieties were used: January Master, Idol, Napolitano Mazartico and Igloo and the planting dates were May, June and July.